SHARIA ACCOUNTING ASSISTANCE FOR THE MANAGEMENT OF SHARIA SAVINGS AND LOAN AND FINANCING COOPERATIVES IN SUBANG DISTRICT - Asep Kurniawan; Rosalia Aghata; Euis Apriliana; Putri Oktaviana; Rianniva Laela Permana; Feby Farichatul Ummah; Nalla Susanti (STIESA-PRESS, 2024)
This sharia accounting assistance program aims to improve the understanding and skills of the management of Sharia Savings and Loan and Financing Cooperatives (KSPPS) in Subang Regency in applying sharia accounting principles correctly and consistently. The program implementation method includes identification of needs through surveys and interviews, preparation of training materials, conducting workshops and intensive training, and making sharia accounting guidelines. Evaluation of program effectiveness was conducted using pre-test and post-test questionnaires. The results of the program showed a significant increase in the understanding and skills of KSPPS management related to sharia accounting, improved transparency and accountability of financial statements, and increased trust of cooperative members. The evaluation revealed that the participatory approach and the use of real case studies in the training were very effective. Constraints encountered included time constraints and different levels of understanding among participants. Recommendations include continuous capacity building, adjusting training methods, strengthening collaboration, and continuous monitoring and evaluation.